INDUSTRIAL HERITAGE AS A RESOURCE FOR SUSTAINABLE DEVELOPMENT OF INDUSTRIAL REGIONS: THE CASE OF KRYVYI RIH - PATSIUK, Viktoriia; KAZAKOV, Volodymyr (Bulletin of Taras Shevchenko National University of Kyiv, Geography, 2025)
Background. In modern conditions of post-industrial territorial transformation, the issue of preserving and re-evaluating industrial heritage gains particular relevance. The decline of functioning industries leaves behind numerous objects that can be either a source of decline or a potential for development. Kryvyi Rih, as one of Ukraine's most prominent industrial regions, has accumulated a significant array of such objects. The aim of this study is to analyze the industrial heritage of Kryvyi Rih as a resource for the sustainable development of the region, identify its potential for preservation and reuse, and outline the key challenges and opportunities for transforming the post-industrial landscape into a hub of public and tourist activity.Methods. The study was conducted based on the theoretical foundations of the International Committee for the Conservation of Industrial Heritage (TICCIH), including the Nizhny Tagil Charter and the Dublin Principles. Historical-geographical analysis, cartography, analysis of archival and field materials, typologization and systematization of objects were applied. Additionally, a research algorithm was developed, encompassing four stages: preparatory, expeditionary, analytical, and conceptual.Results. Within the scope of the study, foreign and Ukrainian discourses on industrial heritage were analyzed. An inventory of over 800 industrial heritage objects in Kryvyi Rih was conducted. Their typologization is proposed based on their subject essence, time of origin, and degree of preservation. A subject classification is presented, which considers manufacturing, infrastructure, social, memorial components, and intangible industrial heritage. Three historical periods of the region's industrial heritage formation and three levels of its preservation have been identified.Conclusions. The industrial heritage of Kryvyi Rih is an integral part of the regional identity and holds significant potential for integration into sustainable development concepts. The proposed research algorithm and classification can be used as a methodological basis for developing programs for the preservation, revitalization, and promotion of industrial heritage. The identified objects form the basis for creating industrial culture clusters, developing industrial tourism and creative industries, and fostering a sustainable urban environment based on local resource potential.
Keywords: industrial heritage; sustainable development; revitalization, industrial spaces; Kryvyi Rih